IMPLEMENTASI MEDIA E-COMIC DALAM MENANAMKAN NILAI-NILAI FILOSOFI SAINS DAN ISLAM PADA SENI REYOG PONOROGO - Susanto, Happy; Arif, Zainal; Muslich, Ahmad; Saputro, Anip Dwi; Laksana, Sigit Dwi; Arifin, Ja’far; Tajab, Muh (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
This study is an effort to look deeper of Reyog Ponorogo art, especially for the next generation, by using e-comic media to instill the values of science and Islamic philosophy. The question arises as why it is necessary for E-Comic to instill the value of science and Islam in the art of Reyog Ponorogo.The purpose of this study is to create an effective and efficient Reyog Ponorogo art learning media to instill the values of the philosophy of science and Islam.The research method used is literature study. Data was also collected through readings related to Reyog Ponorogo art, E-Comic media and the inculcation of the valuesof science and Islamic philosophy.The results showed that to preserve the art of Reyog Ponorogo to the next generation of the nation, an alternative media of e-comic was needed to instill the values of the philosophy of science and Islam.Â